Induction of vasculogenic mimicry overrides VEGF-A silencing and enriches stem-like cancer cells in melanoma - Schnegg, Caroline I. (Cancer Res, 2015)
The basis for resistance to VEGF inhibition is not fully understood despite its clinical importance. In this study, we examined the adaptive response to VEGF-A inhibition by a loss-of-function analysis using plasmid-based shRNA. Tumor xenografts that initially responded to VEGF-A inhibition underwent an adaptation in vivo leading to acquired resistance. VEGF-A blockade in tumors was associated with HIF-1α expression and an increase in CD144(+) vasculogenic mimicry (VM), leading to formation of channels displaying Tie-1 and MMP-2 upregulation. CD133(+) and CD271(+) melanoma stem-like cells (MSLC) accumulated in the perivascular niche. Tumor xenografts of melanoma cell populations that were intrinsically resistant to VEGF-A blockade did not exhibit any of these features, compared to non-target control counterparts. Thus, melanomas which are initially sensitive to VEGF-A blockade acquire adaptive resistance by adopting VM as an alternate angiogenic strategy, thereby enriching for deposition of MSLC in the perivascular niche through a HIF-1α-dependent process. Conversely, melanomas which are intrinsically resistant to VEGF-A blockade do not show any evidence of compensatory survival mechanisms that promote MSLC accumulation. Our work highlights the potential risk of anti-VEGF treatments owing to a selective pressure for an adaptive resistance mechanism that empowers the development of stem-like cancer cells, with implications for how to design combination therapies that can improve outcomes in patients.